Visceral adipose tissue is more strongly associated with insulin resistance than subcutaneous adipose tissue in Chinese subjects with pre-diabetes. (2nd January 2018) - Liu, Lin; Feng, Jitao; Zhang, Gong; Yuan, Xiaodan; Li, Fan; Yang, Tingting; Hao, Shujie; Huang, Dejian; Hsue, Cunyi; Lou, Qinging
Abstract: Aims: To investigate the value of visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) in a cohort of a community's residents who were diagnosed as pre-diabetes, and to evaluate the association of VAT and SAT with insulin resistance. Methods: This study was based on cross-sectional analysis of data from 107 adults. VAT and SAT were assessed by computed tomography. Insulin resistance was defined by homeostasis model assessment of insulin resistance >2.69. The relationship of VAT and SAT with insulin resistance were examined by linear regression. Logistic regression was used to analyze the association of VAT and SAT with insulin resistance. Results: A total of 87 subjects had VAT ≥100 cm 2 . Thirty-six out of 107 (33.6%) subjects were detected to have insulin resistance, 71 were normal (66.4%), and all had insulin resistance with VAT ≥100 cm 2 . VAT ( r = 0.378, p < .001) and SAT ( r = 0.357, p < .001) were significantly and positively correlated with insulin resistance. In multiple regression analysis when VAT and SAT were simultaneously included after adjustment for age, gender, BMI, and WC, the association between VAT and insulin resistance was still maintained ( p = .003), but that of SAT was lost. Conclusion: Pre-diabetic subjects with insulin resistance had elevated levels of VAT. VAT was more strongly associated with insulin resistance than SAT in Chinese subjects with pre-diabetes.